Understanding physiological mechanisms of variation in grain filling of maize under high planting density and varying nitrogen applicate rate - Ren, Hong; Zhao, Ming; Zhou, Baoyuan; Zhou, Wenbin; Li, Kemin; Qi, Hua; Jiang, Ying; Li, Congfeng (Frontiers in Nutrition, 2022)
Grain filling is a critical process for achieving high grain yield in maize (Zea mays L.), which can be improved by optimal combination with genotype and nitrogen (N) fertilization. However, the physiological processes of variation in grain filling between hybrids and the underlying mechanisms of carbon (C) and N translocation, particularly different under various N fertilizations, remain poorly understood. In this study, Xianyu 335 (XY335) and Zhengdan958 (ZD958) were grown with N inputs of 0, 150, and 300 kg N ha-1 (N0, N150, and N300) in a two-year field experiment. Results showed that N application significantly optimized grain-filling parameters for both maize hybrids. In particular, there was an increase in XY335 of the maximum filling rate (Gmax) and the mean grain-filling rate (Gmean) by 8.1% and 7.1% compared to ZD958 under N300 condition, respectively. Simultaneously, N300 increased the small and big vascular bundles area of phloem, and the number of small vascular bundles in peduncle and cob at milking stage for XY335. XY335 significantly increased the root bleeding sap and matter transport efficiency of maize under different N conditions, which greatly enhanced the 13C assimilates and higher C and N in grains to facilitate grain filling compared to ZD958. As a result, the grain yield and the sink capacity for XY335 significantly increased by 6.9 % and 6.4 % compared to ZD958 under N300 conditions. These findings might provide physiological information on appropriate agronomy practices in enhancing the grain-filling rate and grain yield for maize under different N application, namely the optimization variety and N condition noticeably increased grain filling rate after silking by improving ear vascular structure, matter transport efficiency, and enhancing C and N assimilation translocation to grain, eventually a distinct improvement in the grain sink and the grain yield.